Hydrogen Sulfide: A Potent Tool in Postharvest Fruit Biology and Possible Mechanism of Action - Ziogas, Vasileios; Molassiotis, Athanassios; Fotopoulos, Vasileios; Tanou, Georgia (Frontiers in Plant Science, 2018)
Hydrogen sulfide (H2S), an endogenous gaseous molecule, is considered as a signaling agent, in parallel with other low molecular weight reactive substances, mainly hydrogen peroxide (H2O2) and nitric oxide (NO), in various plant systems. New studies are now revealing that the postharvest application of H2S, through H2S donors such as sodium hydrosulfide (NaSH) or sodium sulfide (Na2S), can inhibit fruit ripening and senescence programs in numerous fruits. We discuss here current knowledge on the impact of H2S in postharvest physiology of several climacteric and non-climacteric fruits such as banana, apple, pear, kiwifruit, strawberry, mulberry fruit, and grape. Although there is still a considerable lack of studies establishing the mechanisms by which H2S signaling is linked to fruit metabolism, we highlight several candidate mechanisms, including a putative cross-talk between H2S and ethylene, reactive oxygen and nitrogen species, oxidative/nitrosative stress signaling, sulfate metabolism, and post-translational modification of protein cysteine residues (S-sulfhydration) as being functional in this H2S postharvest action. Understanding H2S metabolism and signaling during postharvest storage and the interplay with other key player molecules would therefore provide new, improved strategies for better fruit postharvest storage. To achieve this understanding, postharvest fruit physiology research will need to focus increasingly on the spatial interaction between H2S and ethylene perception as well as on the interplay between S-sulfhydration/desulfhydration and S-nitrosylation/denitrosylation under several postharvest conditions.